2015
DOI: 10.4300/jgme-07-02-31
|View full text |Cite
|
Sign up to set email alerts
|

The Need for a Leadership Curriculum for Residents

Abstract: The ACGME News and Views section of JGME includes data reports, updates, and perspectives from the ACGME and its review committees. The decision to publish the article is made by the ACGME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 2 publications
0
36
0
Order By: Relevance
“…Numerous sources acknowledge the need for leadership development among trainees, noting that leadership skills can improve health outcomes. 8,9,10 Yet, neither undergraduate nor graduate medical education are consistently designed with formal leadership curricula to prepare trainees for the evolving health care industry. 8,9,10,11 If medical education improved trainee leadership, the health care system would benefit from a cadre of physician leaders; however, this requires significant effort and investment that programs may lack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous sources acknowledge the need for leadership development among trainees, noting that leadership skills can improve health outcomes. 8,9,10 Yet, neither undergraduate nor graduate medical education are consistently designed with formal leadership curricula to prepare trainees for the evolving health care industry. 8,9,10,11 If medical education improved trainee leadership, the health care system would benefit from a cadre of physician leaders; however, this requires significant effort and investment that programs may lack.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,10 Yet, neither undergraduate nor graduate medical education are consistently designed with formal leadership curricula to prepare trainees for the evolving health care industry. 8,9,10,11 If medical education improved trainee leadership, the health care system would benefit from a cadre of physician leaders; however, this requires significant effort and investment that programs may lack. National organizations can provide some of this training, and involving specialty organizations may signal an investment in the trainee and thus increase retention and the robustness of our workforce.…”
Section: Discussionmentioning
confidence: 99%
“…The Tideswell ELIA Program was the right catalyst, one that had been sorely missing before 2015, to help us transform our collective mindset about ascending to leadership roles in our careers from uncertain and apprehensive to informed and empowered. 5 Each of us had personal leadership training goals to fulfill that firmly demanded the generation of a reliable and portable "toolbox" of knowledge and skills and also greater clarity of how others really see us and how we see ourselves as aspiring leaders. In this article, we provide a qualitative description, using but a few of the many affirmatory scholar reflections, of the impact of an aging-focused Tideswell ELIA leadership development program on its participants.…”
Section: Abstract: Leadership Training; Professional Development; Comentioning
confidence: 99%
“…[25][26][27][28][29][30] Validated assessment is needed to demonstrate impact and compare curriculum. 9,14,[31][32][33][34][35][36][37][38][39][40][41][42] A systematic review of leadership training in health care teams found that defining best practices is difficult due to lack of a standard definition of leadership, supporting frameworks, and robust assessments. 35 Though assessments do exist for health care administrators, practicing physicians, and surgeons' nontechnical skills in the operating room (including leadership), there are no published assessment instruments of leadership skills for physicians in residency training programs.…”
Section: Original Articlesmentioning
confidence: 99%